[tex] \times = - 8[/tex]
Explicación paso a paso:
[tex] \times + 3 + 3( \times - 3) = 3 \times + 2 + 2 \times [/tex]
[tex] \times + 3 + 3 \times - 9 = 3 \times + 2 + 2 \times [/tex]
[tex] \times + 3 + 3 \times - 9 = 3 \times + 2 + 2 \times [/tex]
[tex] \times - 6 +3 \times = 3 \times + 2 + 2 \times [/tex]
[tex] \times - 6 + 3 \times = 3 \times + 2 + 2 \times [/tex]
[tex]4 \times - 6 = 3 \times + 2 + 2 \times [/tex]
[tex]4 \times - 6 = 5 \times + 2[/tex]
[tex]4 \times - 6 = 5 \times + 2[/tex]
[tex]4 \times - 6 + 6 = 5 \times + 2 + 6[/tex]
[tex] \times = - 8[/tex]
[tex]hola \: saludos[/tex]